2005
DOI: 10.1517/14656566.6.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Management of hepatitis C virus-related arthritis

Abstract: In recent years, hepatitis C virus-related arthritis (HCVrA) has been recognised as an autonomous rheumatic disorder. Two subsets of the disease have been identified: a polyarthritis involving small joints that resembles rheumatoid arthritis, but is usually milder, and a mono-oligoarthritis that shows an intermittent course and is frequently associated with the presence of cryo-globulins in serum. Few data about HCVrA treatment are reported in the literature. As a consequence, the therapeutic approach for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
0
7
0
2
Order By: Relevance
“…However, treatment focusing on relieving the pain associated with joint inflammation without worsening liver damage caused by HCV has been recommended [45]. Medical treatment may involve the use of nonsteroidal anti-inflammatory drugs (NSAIDs) in patients who do not have a cirrhotic process, cyclooxygenase inhibitors, corticosteroids, disease-modifying antirheumatic drugs, and antiviral therapies [45][46]. Medications such as methotrexate or immunosuppressants have not been recommended, at least as an initial effort, given their toxic effect on the liver [47].…”
Section: Hepatitis C Virus and Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…However, treatment focusing on relieving the pain associated with joint inflammation without worsening liver damage caused by HCV has been recommended [45]. Medical treatment may involve the use of nonsteroidal anti-inflammatory drugs (NSAIDs) in patients who do not have a cirrhotic process, cyclooxygenase inhibitors, corticosteroids, disease-modifying antirheumatic drugs, and antiviral therapies [45][46]. Medications such as methotrexate or immunosuppressants have not been recommended, at least as an initial effort, given their toxic effect on the liver [47].…”
Section: Hepatitis C Virus and Arthritismentioning
confidence: 99%
“…The potential impact of substance abuse and other conditions on this population of patients should be carefully examined. Additionally, well-executed studies are needed to determine which medical treatments optimally reduce pain symptoms and/or treat HCV without interfering with liver health or exacerbating pain [45][46]. Such studies will help providers choose treatment courses that maximize efficacy while minimizing detrimental effects on functioning.…”
Section: Future Researchmentioning
confidence: 99%
“…Описано две формы артрита, ассо-циированного с ВГС: более часто встречающийся аутоим-мунный рецидивирующий олигоартрит при криоглобули-немии и полиартрит, возникающий без криоглобулинемии, как неспецифическое воспалительное проявление хрониче-ского вирусного процесса. В последнем варианте он близок к РА, но отличается более мягким течением [38,39,44,45].…”
Section: гу институт ревматологии рамн москваunclassified
“…Потенциально многие противоревматические препараты гепатотоксичны, поэтому их применение требует особой осторожности. Известно, что иммуносупрессивная терапия может усиливать репликацию вируса и усугублять заболевание печени [3,45,50].…”
Section: гу институт ревматологии рамн москваunclassified
“…joint pain (Palazzi, Olivieri, Cacciatore, Pennese, & D'Amico, 2005), irritability and fatigue (Lang et al, 2006) have been reported. What remains unclear is the actual symptom burden associated with HIV/HCV co-infection.…”
mentioning
confidence: 99%